2014
DOI: 10.1144/sp414.7
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary development and magnetic susceptibility evolution of the Frasnian in Western Belgium (Dinant Synclinorium, La Thure section)

Abstract: Recent opening of the La Thure quarry in Western Belgium allowed the collection of new data from a poorly outcropping area of the Belgian Frasnian platform. The studied section covers an interval extending from the falsiovalis to hassi s.l. Zones. Sedimentological analyses allowed the reconstruction of depositional settings in the northwestern part of the Dinant Synclinorium after the demise of the extended Givetian carbonate platform. Two depositional models are distinguished: (a) siliciclastic drowned platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Therefore, the link between sea-level changes and MS may be more complicated than expected Da Silva et al 2009a;Bábek et al 2013 (Mabille & Boulvain 2007;Da Silva et al 2009a, b;Bábek et al 2010Bábek et al , 2013Koptíková et al 2010a). These findings demonstrate the importance of understanding the depositional setting of facies sampled for MS and the potential pitfalls of comparing MS records from different palaeo-environments (see also Alekseev et al 2015;Grabowski et al 2015;Pas et al 2015;Sardar Abadi et al 2015).…”
Section: Application Of Ms Records As Palaeoenvironmental and Palaeo-mentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the link between sea-level changes and MS may be more complicated than expected Da Silva et al 2009a;Bábek et al 2013 (Mabille & Boulvain 2007;Da Silva et al 2009a, b;Bábek et al 2010Bábek et al , 2013Koptíková et al 2010a). These findings demonstrate the importance of understanding the depositional setting of facies sampled for MS and the potential pitfalls of comparing MS records from different palaeo-environments (see also Alekseev et al 2015;Grabowski et al 2015;Pas et al 2015;Sardar Abadi et al 2015).…”
Section: Application Of Ms Records As Palaeoenvironmental and Palaeo-mentioning
confidence: 87%
“…1a). † Geochemical elements such as Zr, Th, Ti and Al are proxies for changes in source or amount of detrital material or type of weathering (Tribovillard et al 2006;Calvert & Pedersen 2007) and have been compared with MS in order to highlight a detrital origin of this MS signal (Riquier et al 2010;Da Silva et al 2012Ś liwiński et al 2012;Alekseev et al 2015;Grabowski et al 2015;Jadot & Boulvain 2015;Pas et al 2015;Whalen et al 2015). An example is provided in Figure 1b, with a comparison of the MS with the Zr content for two Frasnian sections from Belgium (Da Silva et al 2012).…”
Section: Comparison With Other Proxiesmentioning
confidence: 99%
“…Additionally, Gouwy and Bultynck (2003) indicated that the semialternans, hermanni-cristatus and disparilis Zones are not recognized in the Ardennes due to lack of guide species, but based on graphic correlation method the latter authors were able to locate the boundary between the hermani and the disparilis zones (see p. 326 in Gouwy and Bultynck, 2003 for detailed explanations). The portion of the LT section used for comparison herein covers a slightly shorter interval extending from the lower Givetian Polygnathus varcus Zone to the early Frasnian Palmatolepis falsiovalis Zone (Pas et al, 2015(Pas et al, , 2017. The Burgberg section in the northeastern portion of the Rhenohercynian Massif cut through the southeastern fore-reef fringe of the large atoll-like Brilon Reef Complex and the Hauptgrünsteinzug volcanic complex at the base.…”
Section: Geological Settingmentioning
confidence: 99%
“…The second case study consists of the 184 m thick continuous early Givetian to early Frasnian sequence of the La Thure section (∼ 383-380 Ma, Middle-Late Devonian; De Vleeschouwer and Parnell, 2014;De Vleeschouwer et al, 2015;Pas et al, 2016). The Givetian sequence is composed of bedded limestone, mainly deposited in a shallow-water rimmed shelf characterised by a large set of internal and external rimmed-shelf environments (Pas et al, 2016). The overlying early Frasnian sequence is dominated by shale deposited in a siliciclastic drowned platform .…”
Section: Magnetic Susceptibility From La Thure Section (Givetian Midmentioning
confidence: 99%